The number of discernible colours perceived by protanomalous and deuteranomalous in natural scenes - Linhares, João M. M. (2008)
To address the issue of how much impaired is colour vision of anomalous trichromats relatively to normal trichromats, the number of discernible colours seen by anomalous trichromats was estimated from hyperspectral data of 50 natural scenes. In the computations it was assumed that the anomalous cone sensitivities were derived from normal’s by introducing variable spectral shifts. Thus, for protanomalous the L cone was obtained by shifting the M cone towards long - wavelengths; for deuteranomalous the M cone was obtained by shifting the L cone towards short-wavelengths. For each scene the CIELAB colour volume was estimated from each one of the anomalous sensitivities and then segmented into unitary cubes. The number of discernible colours was obtained by counting the number of non empty unitary cubes. It was estimated that typical protanomalous (shifted by 10 nm) and typical deuteranomalous (shifted by 6 nm) distinguish about 70% and 60%, respectively, of those normal observers do, suggesting that a considerable part of the male population has a considerable impaired colour vision